2019
DOI: 10.1002/ags3.12233
|View full text |Cite
|
Sign up to set email alerts
|

Current topics in liver surgery

Abstract: Liver resection is one of the main treatment strategies for liver malignancies. Mortality and morbidity of liver surgery has improved significantly with progress in selection criteria, development of operative procedures and improvements in perioperative management. Safe liver resection has thus become more available worldwide. We have identified four current topics related to liver resection (anatomical liver resection, laparoscopic liver resection, staged liver resection and chemotherapy‐induced liver injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 116 publications
1
8
0
Order By: Relevance
“…In our study, the use of preoperative chemotherapy has not been associated with increased blood loss during liver resection compared to the patients who underwent upfront surgeries. These results, compared with international studies, showed a similar outcome 10 .…”
Section: Discussionsupporting
confidence: 83%
“…In our study, the use of preoperative chemotherapy has not been associated with increased blood loss during liver resection compared to the patients who underwent upfront surgeries. These results, compared with international studies, showed a similar outcome 10 .…”
Section: Discussionsupporting
confidence: 83%
“…These results support minimally invasive hepatobiliary surgeries such as laparoscopic liver resection as one possible option to reduce wound complication rates. Indeed, the rate of severe complications was similar between open and laparoscopic surgeries, while the total wound complication rate was lower and operation time was shorter with laparoscopic surgery than with open surgery (18)(19)(20). Laparoscopic surgery is thus one feasible option when the tumour extension is preferable for laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Hepatic ischemia-reperfusion (IR) injury commonly occurs during liver transplantation or resection and is considered a leading cause of liver damage and dysfunction. [1][2][3][4][5] The mechanisms of hepatic IR injury have been extensively investigated, but nevertheless remain largely unclear. Furthermore, although anaerobic metabolism, mitochondria, oxidative stress, intracellular calcium overload, liver Kupffer cells (KC), neutrophils, cytokines, and chemokines have been found to be involved in the hepatic IR injury process, effective prevention or treatment in clinical practice is still lacking.…”
Section: Introductionmentioning
confidence: 99%